Brazilian evidence-based guideline for screening, diagnosis, treatment, and follow-up of metabolic dysfunction-associated steatotic liver disease (MASLD) in adult individuals with overweight or obesity: A joint position statement from the Brazilian Society of Endocrinology and Metabolism (SBEM), Brazilian Society of Hepatology (SBH), and Brazilian Association for the Study of Obesity and Metabolic Syndrome (Abeso) - Moreira, Rodrigo Oliveira (2023)
Introduction: Metabolic dysfunction-associated steatotic liver disease (MASLD), previously known as Nonalcoholic fatty liver disease (NAFLD), is one of the most common hepatic diseases in individuals with overweight or obesity. In this context, a panel of experts from three medical societies was organized to develop an evidence-based guideline on the screening, diagnosis, treatment, and follow-up of MASLD. Material and methods: A MEDLINE search was performed to identify randomized clinical trials, meta-analyses, cohort studies, observational studies, and other relevant studies on NAFLD. In the absence of studies on a certain topic or when the quality of the study was not adequate, the opinion of experts was adopted. Classes of Recommendation and Levels of Evidence were determined using prespecified criteria. Results: Based on the literature review, 48 specific recommendations were elaborated, including 11 on screening and diagnosis, 9 on follow-up, 14 on nonpharmacologic treatment, and 14 on pharmacologic and surgical treatment. Conclusions: A literature search allowed the development of evidence-based guidelines on the screening, diagnosis, treatment, and follow-up of MASLD in individuals with overweight or obesity.